Implementasi Pembelajaran Immersive Menggunakan Virtual Reality Space - Ibnu Hartopo; Nurul Fahmi Arief Hakim; Silmi Ath Thahirah Al Azhima; Mariya Al Qibtiya; Resa Pramudita; Erik Haritman; Andre Reyvaldo Iglesias (Universitas Ekuitas Indonesia, 2026)
This community service program is motivated by the low level of teachers’ competence in implementing immersive technology-based learning, particularly in utilizing Virtual Reality (VR) as an innovative learning medium. The partner institutions face several challenges, including a limited understanding of immersive learning concepts, a lack of skills in operating VR devices, minimal innovation in teaching methods, and the absence of continuous support in integrating technology into classroom practices. Therefore, this program aims to enhance teachers’ competencies through the utilization of Virtual Reality Space in immersive learning. The program involved 20 teachers from various subject areas and was conducted through several stages: preparation, training and implementation, evaluation, and follow-up. The proposed solutions include training on the fundamental concepts of immersive learning, hands-on workshops on VR device operation, mentoring in developing VR-based instructional designs, and the establishment of a community of practice to ensure sustainability. The results indicate a significant improvement in teachers’ understanding, skills, and readiness to integrate VR into their teaching practices. Evaluation through pre- and post-training questionnaires showed highly positive responses, with an average satisfaction rate of 87%. These findings suggest that VR-based immersive learning effectively enhances teacher-student interaction, increases student engagement, and improves students’ conceptual understanding. Furthermore, this program contributes to strengthening teachers’ digital literacy and promotes the sustainable adoption of innovative technologies in the partner schools. Keyword: immersive learning, virtual reality, training, teacher competence, educational innovation Abstrak Program pengabdian kepada masyarakat ini dilatarbelakangi oleh rendahnya kompetensi guru dalam mengimplementasikan pembelajaran berbasis teknologi immersive, khususnya dalam pemanfaatan Virtual Reality (VR) sebagai media pembelajaran inovatif. Mitra menghadapi beberapa permasalahan, antara lain keterbatasan pemahaman terhadap konsep pembelajaran immersive, kurangnya keterampilan dalam mengoperasikan perangkat VR, minimnya inovasi dalam metode pembelajaran, serta belum adanya dukungan berkelanjutan dalam mengintegrasikan teknologi ke dalam praktik pembelajaran di kelas. Oleh karena itu, program ini bertujuan untuk meningkatkan kompetensi guru melalui pemanfaatan Virtual Reality Space dalam pembelajaran immersive. Program ini melibatkan 20 guru dari berbagai bidang mata pelajaran dan dilaksanakan melalui beberapa tahapan, yaitu persiapan, pelatihan dan implementasi, evaluasi, serta tindak lanjut. Solusi yang ditawarkan meliputi pelatihan konsep dasar pembelajaran immersive, workshop praktik penggunaan perangkat VR, pendampingan dalam pengembangan desain pembelajaran berbasis VR, serta pembentukan komunitas praktisi untuk menjamin keberlanjutan program. Hasil kegiatan menunjukkan adanya peningkatan yang signifikan dalam pemahaman, keterampilan, dan kesiapan guru untuk mengintegrasikan VR ke dalam praktik pembelajaran. Evaluasi melalui kuesioner pra dan pascapelatihan menunjukkan respons yang sangat positif, dengan tingkat kepuasan rata-rata mencapai 87%. Temuan ini mengindikasikan bahwa pembelajaran immersive berbasis VR efektif dalam meningkatkan interaksi antara guru dan siswa, meningkatkan keterlibatan siswa, serta memperdalam pemahaman konsep pembelajaran. Selain itu, program ini juga berkontribusi dalam memperkuat literasi digital guru dan mendorong adopsi teknologi inovatif secara berkelanjutan di sekolah mitra. Kata kunci: pembelajaran immersive, virtual reality, pelatihan, kompetensi guru, inovasi pendidikan